2014
DOI: 10.1590/s0100-736x2014001000017
|View full text |Cite
|
Sign up to set email alerts
|

Systematization, distribution and territory of the caudal cerebral artery on the brain's surface of the turkey (Meleagris gallopavo)

Abstract: Thirty Meleagris gallopavo heads with their neck segments were used. Animals were contained and euthanized with the association of mebezonium iodide, embutramide and tetracaine hydrochloride (T 61, Intervet ) by intravenous injection. The arterial system was rinsed with cold saline solution (15°C), with 5000IU heparin and filled with red-colored latex. The samples were fixed in 20% formaldehyde for seven days. The brains were removed with a segment of cervical spinal cord and after, the dura-mater was removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…In the ostrich, the hemispheric terminal branch of the middle cerebral artery projected ventrally onto the lateral side of the convex face of the cerebral hemisphere, toward the olfactory bulb, terminating, in most cases, by advancing slightly into the lateral territory of the olfactory bulb. In the turkey, the terminal hemispheric branch of the middle cerebral artery, called the rostral hemispheric branch, rose to the convex face to vascularize the most rostral third of the sagittal eminence, where its terminal branches were anastomosed “ in osculum ” with the terminal branches of the final dorsal hemispheric vessel, a branch of the interhemispheric artery (Carvalho and Campos, ). For Campos (), in Gallus gallus, the main terminal branch of the middle cerebral artery divided into two main trunks at the height of the olfactory bulb, called the medial and lateral rostral hemispheric branches.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the ostrich, the hemispheric terminal branch of the middle cerebral artery projected ventrally onto the lateral side of the convex face of the cerebral hemisphere, toward the olfactory bulb, terminating, in most cases, by advancing slightly into the lateral territory of the olfactory bulb. In the turkey, the terminal hemispheric branch of the middle cerebral artery, called the rostral hemispheric branch, rose to the convex face to vascularize the most rostral third of the sagittal eminence, where its terminal branches were anastomosed “ in osculum ” with the terminal branches of the final dorsal hemispheric vessel, a branch of the interhemispheric artery (Carvalho and Campos, ). For Campos (), in Gallus gallus, the main terminal branch of the middle cerebral artery divided into two main trunks at the height of the olfactory bulb, called the medial and lateral rostral hemispheric branches.…”
Section: Discussionmentioning
confidence: 99%
“…In the turkey, the rostral cerebral artery in the right antimere displayed a medium development in 50% of cases to the right antimere and a small development in 43.3% of specimens in the left antimere. In cases in which the development was small, the vascular territorial area was compensated by the ventral hemispheric branches of the middle cerebral artery, which were more developed (Carvalho and Campos, ). Vitums et al () found that in sparrows, after originating in the middle and caudal cerebral artery, the rostral branch abruptly projected medially, approaching the brain's interhemispheric fissure in the pre‐optic groove, where the rostral branch gave rise to a cerebral rostral artery, continuing as an ethmoidal artery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations